Predictors and Management of Loss of Response to Vedolizumab in Inflammatory Bowel Disease. Issue 11 (18th May 2018) - Shmidt, Eugenia; Kochhar, Gursimran; Hartke, Justin; Chilukuri, Prianka; Meserve, Joseph; Chaudrey, Khadija; Koliani-Pace, Jenna L; Hirten, Robert; Faleck, David; Barocas, Morris; Luo, Michelle; Lasch, Karen; et al.
Abstract: Background: We quantified loss of response (LOR) to vedolizumab (VDZ) in clinical practice and assessed the effectiveness of VDZ dose intensification for managing LOR. Methods: Retrospective review (May 2014–December 2016) of a prospectively maintained inflammatory bowel disease (IBD) registry. Kaplan-Meier estimates were used to determine rates of LOR to VDZ . Independent predictors of LOR were identified using univariate and multivariable Cox proportional hazard regression. Success of recapturing response (>50% reduction in symptoms from baseline) and remission (complete resolution of symptoms) after dose intensification was quantified. Results: Cumulative rates for VDZ LOR were 20% at 6 months and 35% at 12 months, with slightly lower rates in Crohn's disease than in ulcerative colitis (6 months 15% vs 18% and 12 months 30% vs 39%, P = 0.03). On multivariable analysis, LOR to a tumor necrosis factor (TNF) antagonist before VDZ use was associated with an increased risk for LOR to VDZ [hazard ratio (HR) 1.93; 95% confidence interval (CI) 1.25–2.97] in all patients. For Crohn's disease patients specifically, higher baseline C-reactive protein concentration was associated with increased risk for LOR to VDZ (HR 1.01 per mg/dL increase, 95% CI 1.01–1.02). Shortening of VDZ infusion interval from 8 to every 4 or 6 weeks recaptured response in 49% and remission in 18% of patients. Conclusions: LOR to a TNF antagonist before VDZ use and higher baseline C-reactive protein are important predictors of VDZ LOR. Treatment response can be recaptured in almost half of these patients with VDZ infusion interval shortening.